Experimental transmission of piscine orthoreovirus-1 (PRV-1) in different life stages of Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) - Kannimuthu, Dhamotharan; Roh, HyeongJin; Morton, H Craig; Peñaranda, Ma Michelle D.; Vossgård, Anne; Hansen, Tom; Fjelldal, Per Gunnar; Karlsbakk, Egil; Fiksdal, Ingrid; Dahle, Maria K.; Berg-Rolness, Håkon; Mæhle, Stig; et al. (Frontiers in Marine Science, 2023)
Piscine orthoreovirus -1 (PRV-1) causes the disease heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon, and the virus has been detected in wild anadromous Atlantic salmon and brown trout. However, the infection prevalence, viral kinetics, and disease severity in different life stages of Atlantic salmon and brown trout are unknown. The current study aimed to evaluate and compare susceptibility to PRV-1 infection and development of HSMI in different life stages of anadromous Atlantic salmon (Salmo salar) and brown trout (Salmo trutta). We challenged Atlantic salmon and brown trout fry, parr, and post-smolts with PRV-1 by bath, cohabitation, or IP injection. The kinetics of viral infection and disease development were evaluated by RT-qPCR, in situ hybridization, and histology. Our results indicated that PRV-1 infection prevalence and viral kinetics depend on the developmental stage and challenge method in both Atlantic salmon and brown trout. All developmental stages of Atlantic salmon and brown trout can be infected with PRV-1. However, brown trout showed a lower infection prevalence, with positive cases exhibiting only mild infections without any pathological changes in the target organs, while all life stages of Atlantic salmon developed heart lesions characteristic of HSMI. These results strongly suggest that brown trout are less susceptible to PRV-1 infection than Atlantic salmon and further confirm the species-specific susceptibility and disease development for PRV-1 infection.